2017
DOI: 10.1016/j.jtho.2016.11.1122
|View full text |Cite
|
Sign up to set email alerts
|

P2.01-070 Circulating Biomarkers of Frailty Are Associated with a Poor Prognosis in Patients with Advanced Non-Small Cell Lung Cancer (NSCLC)

Abstract: CAFs increases tumor growth while knockdown of CNTFR in lung tumor cells decreases overall growth. With the use of advanced protein engineering technology, we generated a high-affinity CNTFR decoy that inhibits CLCF1-CNTFR signaling and are currently testing this novel reagent to elucidate the mechanism by which CNTFR activation alters intercellular signaling to increase tumor cell growth. Through in vivo studies with cell lines and PDXs, we are also exploring the efficacy of this CNTFR decoy as a form of lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…In this cohort, a series of blood tests have been shown to predict the frailty and subsequent mortality [32]. The pilot work then showed key differences in these blood tests in patients with lung cancer from the Newcastle 85+ cohort and showed that they can predict mortality [33]. In addition, sarcopenia is a key element of frailty, and this was investigated in Newcastle by assessing grip strength which when adjusted for age and gender has a prognostic value in cancer patients awaiting clinical trials [34].…”
Section: Newcastle Upon Tynementioning
confidence: 99%
“…In this cohort, a series of blood tests have been shown to predict the frailty and subsequent mortality [32]. The pilot work then showed key differences in these blood tests in patients with lung cancer from the Newcastle 85+ cohort and showed that they can predict mortality [33]. In addition, sarcopenia is a key element of frailty, and this was investigated in Newcastle by assessing grip strength which when adjusted for age and gender has a prognostic value in cancer patients awaiting clinical trials [34].…”
Section: Newcastle Upon Tynementioning
confidence: 99%
“…No carcinoma pulmonar de células não pequenas (NSCLC), biomarcadores, incluindo comprimento de telômero, adiponectina, PCR de alta sensibilidade, proteína ligadora de IGF-1, Fator de Crescimento Transformador Beta (TGF-B), alfa-1 glicoproteína ácida e ligante Tirosino-quinase 3 Fms-relacionado (FLT3) foram biomarcadores circulantes de fragilidade que se correlacionaram com um mau prognóstico em pacientes com NSCLC. 34 A Interleucina-6 I é outro marcador promissor na previsão de fragilidade.…”
Section: Biomarcadores De Fragilidade Em Estudos De Câncerunclassified